Verify that the given differential equation is not exact. (−xy sin(x) + 2y cos(x)) dx + 2x cos(x) dy = 0 If the given DE is written in the form M(x, y) dx + N(x, y) dy = 0, one has My = Nx = . Since My and Nx equal, the equation is not exact. Multiply the given differential equation by the integrating factor μ(x, y) = xy and verify that the new equation is exact. If the new DE is written in the form M(x, y) dx + N(x, y) dy = 0, one has My = Nx = . Since My and Nx equal, the equation is exact. Solve.

Respuesta :

The ODE

[tex]M(x,y)\,\mathrm dx+N(x,y)\,\mathrm dy=0[/tex]

is exact if

[tex]\dfrac{\partial M}{\partial y}=\dfrac{\partial N}{\partial x}[/tex]

We have

[tex]M=-xy\sin x+2y\cos x\implies M_y=-x\sin x+2\cos x[/tex]

[tex]N=2x\cos x\implies N_x=2\cos x-2x\sin x[/tex]

so the ODE is indeed not exact.

Multiplying both sides of the ODE by [tex]\mu(x,y)=xy[/tex] gives

[tex]\mu M=-x^2y^2\sin x+2xy^2\cos x\implies(\mu M)_y=-2x^2y\sin x+4xy\cos x[/tex]

[tex]\mu N=2x^2y\cos x\implies(\mu N)_x=4xy\cos x-2x^2y\sin x[/tex]

so that [tex](\mu M)_y=(\mu N)_x[/tex], and the modified ODE is exact.

We're looking for a solution of the form

[tex]\Psi(x,y)=C[/tex]

so that by differentiation, we should have

[tex]\Psi_x\,\mathrm dx+\Psi_y\,\mathrm dy=0[/tex]

[tex]\implies\begin{cases}\Psi_x=\mu M\\\Psi_y=\mu N\end{cases}[/tex]

Integrating both sides of the second equation with respect to [tex]y[/tex] gives

[tex]\Psi_y=2x^2y\cos x\implies\Psi=x^2y^2\cos x+f(x)[/tex]

Differentiating both sides with respect to [tex]x[/tex] gives

[tex]\Psi_x=-x^2y^2\sin x+2xy^2\cos x=2xy^2\cos x-x^2y^2\sin x+\dfrac{\mathrm df}{\mathrm dx}[/tex]

[tex]\implies\dfrac{\mathrm df}{\mathrm dx}=0\implies f(x)=c[/tex]

for some constant [tex]c[/tex].

So the general solution to this ODE is

[tex]x^2y^2\cos x+c=C[/tex]

or simply

[tex]x^2y^2\cos x=C[/tex]

We are to verify and confirm if the given differential equations are exact or not. Then solve for the exact equation.

The first differential equation says:

[tex]\mathbf{(-xy \ sin x + 2y \ cos x) dx + 2(x \ cos x) dy = 0 }[/tex]

Recall that:

A differential equation that takes the form [tex]\mathbf{M(x,y)dt + N(x, y)dy = 0 }[/tex] will be exact if and only if:

  • [tex]\mathbf{\dfrac{\partial M }{\partial y} = \dfrac{\partial N }{\partial x}}[/tex]

From equation (1), we can represent M and N as follows:

  • [tex]\mathbf{M = (-xy \ sin x + 2y \ cos x)}[/tex]
  • [tex]\mathbf{N = (2x \ cos x)}[/tex]    

Thus, taking the differential of M and N, we have:

[tex]\mathbf{ \dfrac{\partial M}{\partial y }= M_y = -x sin x + 2cos x}[/tex]

[tex]\mathbf{ \dfrac{\partial N}{\partial x }= N_x = 2 cos x + 2x sin x}[/tex]

From above, it is clear that:

[tex]\mathbf{\dfrac{\partial M }{\partial y} \neq \dfrac{\partial N }{\partial x}}[/tex]

We can conclude that the equation is not exact.

Now, after multiplying the given differential equation in (1) by the integrating factor μ(x, y) = xy, we have:

  • [tex]\mathbf{ = \mathsf{(-x^2y^2 sin x + 2xy^2cos x ) dx +(2x^2ycos x ) dy = 0 --- (2)}}[/tex]

Representing the equation into form M and N, then:

[tex]\mathbf{M = -x^22y^2 sin x +2xy^2 cos x}[/tex]

[tex]\mathbf{N = 2x^2y cos x}[/tex]

Taking the differential, we have:

[tex]\mathbf{\dfrac{\partial M}{\partial y }= M_y = -2x^2y sin x + 4xy cos x }[/tex]

[tex]\mathbf{\dfrac{\partial N}{\partial x} =N_x= 4xycos \ x -2x^2 y sin x}[/tex]

Here;

[tex]\mathbf{\dfrac{\partial M}{\partial y} = \dfrac{\partial N}{\partial x} }[/tex]

Therefore, we can conclude that the second equation is exact.

Now, the solution of the second equation is as follows:

[tex]\int_{y } M dx + \int (not \ containing \ 'x') dy = C[/tex]

[tex]\rightarrow \int_{y } (-x^2y^2 sin(x) +2xy^2 cos (x) ) dx + \int(0)dy = C[/tex]

[tex]\rightarrow-y^2 \int x^2 sin(x) dx +2y ^2 \int x cos (x) dx = C[/tex]    ---- (3)

Taking integrations by parts:

[tex]\int u v dx = u \int v dx - \int (\dfrac{du}{dx} \int v dx) dx[/tex]

[tex]\int x^2 sin (x) dx = x^2 \int sin(x) dx - \int (\dfrac{d}{dx}(x^2) \int (sin \ (x)) dx) dx[/tex]

[tex]\to x^2 (-cos (x)) \ - \int 2x (-cos \ (x)) \ dx[/tex]

[tex]\to -x^2 (cos (x)) \ + \int 2x \ cos \ (x) \ dx[/tex]   ----- replace this equation into (3)

[tex]\rightarrow-y^2( -x^2 cos (x) \ + \int 2x \ cos \ (x) \ dx) +2y ^2 \int x cos (x) dx = C[/tex]

[tex]\mathbf{\rightarrow -x^2 y^2 cos (x) \ -2y ^2 \int x \ cos \ (x) \ dx +2y ^2 \int x cos (x) dx = C}[/tex]

[tex]\mathbf{x^2y^2 cos (x) = C\ \text{ where C is constant}}[/tex]

Therefore, from the explanation, we've can conclude that the first equation is not exact and the second equation is exact.

Learn more about differential equations here:

https://brainly.com/question/353770?referrer=searchResults

ACCESS MORE